Hydrodynamic and energy extraction properties of oscillating hydrofoil with double Fowler flaps - Sun, Guang; Zhang, Qiang; Sun, Hongyuan; Chi, Mingshan; Liu, Gang (Frontiers in Marine Science, 2025)
In order to improve the energy extraction capability of oscillating hydrofoils, a dual Fowler flap structure is adopted as a device to increase lift. According to the motion of the oscillating hydrofoil, the double Fowler flaps retract and swing to increase the chord length and curvature of the entire hydrofoil. We proposed and established the structure and motion equation of Fowler flaps, and studied the influence of Fowler flaps on the overall performance of hydrofoils under fixed Reynolds number conditions. The numerical results indicate that compared to the NACA0018 hydrofoil without flaps, the application of Fowler flaps increase overall wing camber. By influencing the flow structure and pressure distribution around the trailing edge of the hydrofoil, Fowler flaps help generate lift, resulting in higher power coefficient and energy capture efficiency. The structure of the Fowler flaps keeps the entire hydrofoil in the streamlined state of traditional hydrofoils, with a smaller range of fluctuations in lift and drag.